Using ethanol and other lures to monitor invasive ambrosia beetles in endemic populations: case study from the Czech Republic - Fiala, Tomáš; Pyszko, Petr; Holuša, Jaroslav (Frontiers in Forests and Global Change, 2023)
Bark and ambrosia beetles pose significant threats to the stability of forest stands worldwide, making their control crucial. Among these pests, Gnathotrichus materiarius, a polyphagous invasive bark ambrosia beetle living on conifers, has successfully established itself in Europe. Early identification of these pests plays a fundamental role in designing effective pest control strategies. The work aimed to assess the efficacy of different lures in Ecotrap ® for capturing of invasive ambrosia bark beetles. The lures tested included Wood Stainers Lure (containing the potential pheromone sulcatol for capturing Gnathotrichus materiarius adults), α-pinene, ethanol UHR, and Cembräwit. The objective was to determine the most suitable lure for use in traps. In four locations in western Bohemia, a total of 7410 individuals from 45 46 species of ambrosia and bark beetles, along with one species of pinhole borer, were captured. The abundance of invasive ambrosia beetles (Gnathotrichus materiarius, Cyclorhipidion bodoanum, Xyleborinus attenuatus, and Xylosandrus germanus) primarily depended on the day of the season and secondarily on the lure used. Although their population density was low, more beetles were caught using ethanol as the lure. Notably, these invasive ambrosia beetles accounted for less than three percent of the total number of ambrosia and bark beetles detected (187 individuals). Ethanol was found to be a universal lure for attracting ambrosia and bark beetles, with the majority of Scolytinae species being captured in traps baited with ethanol.